2019
DOI: 10.25083/rbl/24.2/366.373
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk in patients with inflamma-tory bowel diseases: a review

Abstract: Patients with inflammatory bowel diseases (IBD) have an increased risk of cardiovascular events (myocardial infarction, cerebrovascular events and death of cardiovascular causes), because of some common pathophysiological mechanisms. Patients with IBD have high levels of cytokines, C-reactive protein and homocysteine, leading to endothelial dysfunction and atherosclerosis. Also, the increased levels of coagulation factors in patients with IBD lead to an increased risk for thromboembolic events. There are numer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 52 publications
0
7
0
2
Order By: Relevance
“…A systematic review across 33 studies found no increased risk of arterial TEs (relative risk: 1.15, 95% CI 0.91, 1.45) [21]. However, to date, results regarding the risk of arterial TEs in patients with IBD have been inconsistent due to factors such as type of arterial TE, severity of IBD and patient characteristics [4,21,22]. The baseline period was defined as 1-year period prior to the index date b…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review across 33 studies found no increased risk of arterial TEs (relative risk: 1.15, 95% CI 0.91, 1.45) [21]. However, to date, results regarding the risk of arterial TEs in patients with IBD have been inconsistent due to factors such as type of arterial TE, severity of IBD and patient characteristics [4,21,22]. The baseline period was defined as 1-year period prior to the index date b…”
Section: Discussionmentioning
confidence: 99%
“…Patients who experience fatigue also evaluate their disease as having more negative consequences and a higher emotional impact, than patients who do not experience this symptom. This is understandable as fatigue has crippling effects on one's social and work life, also impacting the general well-being (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies suggest that patients with IBD have an increased risk for developing myocardial infarction and stroke 15,16 . In addition, these patients are at high risk of developing cardiovascular events in the perioperative period, and they are in need for a specifi c anesthesia and intensive care management, especially related to surgery [17][18][19] .…”
Section: Surgical Indications and Optionsmentioning
confidence: 99%